Bonniers novels II (1980–81) - Språkbanken Text (University of Gothenburg, 2024)
A corpus of 60 Bonnier novels from 1980–81

En korpus med 60 Bonniersromaner från 1980–81
Bonniersromaner II (1980–81)
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik